Evaluation of the Potential for QTc Prolongation With Repeated Oral Doses of Fedratinib in Patients With Advanced Solid Tumors. Issue 4 (16th July 2020) - Ogasawara, Ken; Xu, Christine; Yin, Jian; Darpo, Borje; Carayannopoulos, Leon; Xue, Hongqi; Palmisano, Maria; Krishna, Gopal
Abstract: The impact of repeated daily 500‐mg fedratinib (an oral selective Janus kinase [JAK] 2 inhibitor) on QTc and other electrocardiogram (ECG) parameters was assessed in 60 patients with advanced solid tumors. Patients received placebo on day 1 and fedratinib 500 mg daily for 14 days. Concentration‐QTc analysis was performed with change‐from‐baseline QTc corrected by Fridericia's formula (ΔQTcF) as the dependent variable. Fedratinib median time to maximum plasma concentration (Cmax ) was observed 3 hours postdose on day 15. The largest difference between means for fedratinib and placebo was 0.5 bpm (90%CI, −2.75 to 3.72 bpm) for heart rate (3 hours postdose) and 4.3 milliseconds (90%CI, 1.04‐7.60 milliseconds) for QTcF (4 hours postdose). The estimated slope of the fedratinib concentration‐QTcF relationship was shallow and not statistically significant: −0.0005 milliseconds per ng/mL (90%CI, −0.00145 to 0.00050 milliseconds per ng/mL). Predicted fedratinib placebo‐corrected ΔQTcF was 0.6 milliseconds (90%CI, −1.80 to 2.93 milliseconds) at the geometric mean of the observed Cmax (3615 ng/mL). Fedratinib did not affect PR or QRS intervals. No patients had QTcF > 60 milliseconds, and no patients experienced QTcF ≥ 500 milliseconds. Fedratinib did not cause clinically relevant ECG effects or QTc prolongation. Safety findings were consistent with the known safety profile.